Seasonal variation in pediatric dermatoses - Banerjee Sabyasachi; Gangopadhyay Dwijendra Nath; Jana Sukumar; Chanda Mitra (Wolters Kluwer Medknow Publications, 2010)
Introduction: The under-five population is a unique and vulnerable component of our society that always demands special attention. Aims: Our present work aimed to study the seasonal variation, age-wise variation and distribution of lesions of common dermatoses of this age group. Materials and Methods: We clinically studied all fresh cases attending the skin OPD of our hospital for one month each from summer, rainy season and winter. Total number of patients was 879. Results: The top six skin diseases in our study were impetigo, miliaria, scabies, furunculosis, seborrheic dermatitis and papular urticaria. On statistical analysis, scabies and seborrheic dermatitis were more prevalent during winter while impetigo, furunculosis and miliaria were more during summer and rainy season. Papular urticaria was more frequent in the rainy season. Seborrheic dermatitis predominantly affected the infants while impetigo, furunculosis, miliaria and popular urticaria were commoner in older age groups. Conclusion: Distribution of lesions of common dermatoses will help diagnose difficult cases and extensive evaluation of the body parts which, by virtue of being commonly affected, are must-examine sites in under-five children.